(untitled) (The Journal of Academic Development, 2025)
This study examines the financial structure of Nepali film production, focusing on key cost elements such as pre-production planning, cast and crew salaries, set design, shooting and post-production processes. Article serves as a resource for filmmakers, investors, and scholars interested in understanding the economics of Nepali cinema and offers insights into how cost management affects film quality and commercial success. The goal here is to understand the production cost as well as film making process in Nepal and estimated production cost of Nepali feature films. The four basic and essential stages of production process are classified as development, pre-production, production and post-production. This article uses different methods for analysis: descriptive & comparative methods look at many sides of production; deductive-inductive methods dig deeper; then there’s logical analysis based on existing literature in film production and accounting. It includes informal interviews with film producers as well. The expenses across various filmmaking stages are pretty similar around the globe. The timeframe and structure really play a role in determining production cost. A realistic and accurate budget can help secure financing, avoid overspending, and manage expectations.